2009
DOI: 10.1002/adma.200990174
|View full text |Cite
|
Sign up to set email alerts
|

Liquid‐Crystal Patterning: Lithographic Alignment of Discotic Liquid Crystals: A New Time–Temperature Integrating Framework (Adv. Mater. 46/2009)

Abstract: Liquid crystals are a successful example of how the control of self-assembly via chemical design leads to novel applications. Massimiliano Cavallini, Fabio Biscari, and co-workers report that direct patterning of a continuous metal-free mesogenic phthalocyanine fi lm (discotic LCs) is achieved by spatial control of column orientation using unconventional lithography. These patterned fi lms work as time-temperature integrators at the columnar rectangularhexagonal transition temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…On the other hand, if the phthalocyanine film is confined between two identical substrates, whatever their surface energy or roughness, homeotropic alignment was detected in most cases. A lithographic alignment of phthalocyanine-derived liquid crystals as a time–temperature integrating framework, which is a crucial element for device performance, was reported by Cavallini et al…”
Section: Classes Of Compoundsmentioning
confidence: 99%
“…On the other hand, if the phthalocyanine film is confined between two identical substrates, whatever their surface energy or roughness, homeotropic alignment was detected in most cases. A lithographic alignment of phthalocyanine-derived liquid crystals as a time–temperature integrating framework, which is a crucial element for device performance, was reported by Cavallini et al…”
Section: Classes Of Compoundsmentioning
confidence: 99%
“…Dewetting is an irreversible process that requires activation energy and displays a temperature- and time- dependent characteristic length scale; the ideal prerequisites for TTI applications. An example was reported by Calò et al, in which it is demonstrated how a patterned thin film of polyisobutylene acts as a TTI device . The polymeric film was patterned by electron irradiation of spatially defined zones by an electron beam (Figure a–f).…”
Section: Ttis Based On Morphological Transitionsmentioning
confidence: 91%
“…An example was reported by Calòet al, in which it is demonstrated how a patterned thin film of polyisobutylene acts as a TTI device. 33 The polymeric film was patterned by electron irradiation of spatially defined zones by an electron beam (Figure 3a−f). Upon controlled irradiation, polymer chains fragment, generating zones with controlled (reduced) molecular weight.…”
Section: Ttis Based On Morphological Transitionsmentioning
confidence: 99%
See 2 more Smart Citations